STRENGTHENING THE STUDENTS’ INDEPENDENT ATTITUDES IN LEARNING - Oktaviola; Aswadi Jaya; Mega Prasrihamni (Esteem Journal of English Education Study Programme, 2024)
The purpose of this study is to ascertain how the project to raise the Pancasila student profile (p5) has affected the class IV pupils at SDN 10 Sungailiat's autonomous attitude.Quantitative experimental procedures are the research approach that is employed. Questionnaires are the method used in this study to collect data. This study uses a quasi-experimental design with a posttest alone and a non-equivalent control group. The average posttest score for the control class is 51.37, whereas the experimental class's posttest score is 83.96, according to data processing results from the research. The sample is drawn from a population that is regularly distributed, according to the results of the normality test. The results of the homogeneity test demonstrate that each group's variance is the same, or homogeneous. The results of the independent sample t-test hypothesis test show nvalue of significance2-tailednamely 0.000 so Sig. 0,000< 0.05 with a value of tcount 35.217 and ttable 2.00575 so tcount > ttable. Thus Ho is rejected and Ha is accepted, which means there is influenceproject to strengthen the profile of Pancasila students (p5) towards the independent attitude of class IV students at SDN 10 Sungailiat.